Photocatalytic degradation of herbicide by using aeroxide®P-90 TiO2 photocatalyst and photo-fenton process in the presence of artificial and solar radiation - Telang, T.; Deosarkar, M.P.; Shetty, R.; Kamble, S.P. (Novel water treatment and separation methods: simulation of chemical processes, 2017)
The presence of herbicide residues in the aquatic environment is an emerging issue due to their uncontrolled release through water and accumulation in the environment that may affect living organisms, environment, and public health. Consequently, the efforts are being made to develop the viable methods to eliminate the herbicides from the environment. The degradation of herbicide particularly amitrole has been investigated in aqueous solutions by using artificial and solar radiation. The effect of Aeroxide TiO2 P-90 photocatalyst loading (1-4 g L-1) on photocatalytic degradation of amitrole (50 mg L-1) was investigated. The degradation of amitrole (initial concentration ranging from 20 to 100 mg L-1) also studied by using photo-Fenton process (FeSO4 (10-30 mg L-1) and H2O2 (100-300 mg L-1)). The effect of pH (3-11), effect of co-existing salts (ammonium sulfate, sodium chloride, and sodium carbonate) as well as effect of type of radiation (artificial or solar radiation) on the degradation of amitrole was evaluated and optimized. The degradation of amitrole was accompanied by formation of intermediates which were detected by LC-MS. According to the results presented in this study, the photo-Fenton process using solar radiation is an efficient technique for degradation of amitrole.